Social networks : models of information influence, control and confrontation /: models of information influence, control and confrontation. ([2019]) - Chkhartishvili, A. G (Aleksandr Gedevanovich); Gubanov, Dmitry; Novikov, D. A (Dmitriĭ Aleksandrovich), 1970-
No abstract available